Noel Deisch papers - Deisch, Noel, 1892-1978.
Typescript with holograph notes and corrections of Deisch's monograph, The Navigation of Interplanetary Space: A Study of the Question (Problem) of Flights to Other Worlds (1926), the first serious scientific treatise in English on space travel; together with correspondence, articles, biographical material, and other papers relating to Deisch's patents and awards.
Patent drafter. Full name: John Noel Deisch.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Interplanetary voyages; Space flight; Drafters